2019
DOI: 10.47210/bjohns.2019.v27i3.6
|View full text |Cite
|
Sign up to set email alerts
|

Laryngopharyngeal Reflux: Inter-rater Reliability of Reflux Finding Score in Clinical Practice

Abstract: Introduction Laryngopharyngeal reflux (LPR) is a clinical entity, caused due to retrograde flow of gastric content into the larynx. It imposes great diagnostic challenge to clinicians because of lack of specific symptoms, signs and validated tool. Reflux Finding Score (RFS) has been proposed for clinical diagnosis of LPR. Inter observer reliability of RFS tool was found out using two independent observers Materials and Methods  In this Cross sectional study, ninety LPR subjects were subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…14 Various studies have found that the RFS as a clinical tool for diagnosis of LPR should be viewed with limited utility as it exhibits low inter-rater reliability. 15 Thus, it becomes all the more necessary that the RSI be assessed extensively for symptomatic betterment of the patient.…”
Section: Movementmentioning
confidence: 99%
“…14 Various studies have found that the RFS as a clinical tool for diagnosis of LPR should be viewed with limited utility as it exhibits low inter-rater reliability. 15 Thus, it becomes all the more necessary that the RSI be assessed extensively for symptomatic betterment of the patient.…”
Section: Movementmentioning
confidence: 99%